2019
DOI: 10.1590/0100-29452019018
|View full text |Cite
|
Sign up to set email alerts
|

Defoliation, application of S-ABA and vegetal extracts on the quality of grape and wine Malbec cultivar

Abstract: High rainfall and low temperatures can cause grapes not to reach adequate maturation indexes. The aim of this work was to evaluate the effect of leaf removal, hormonal regulator and vegetable extracts on the quality of grape and wine. An experiment was conducted in a vineyard of Malbec cv.in southern Brazil by two consecutive seasons. Treatments were: 1) control, 2) manual defoliation in early maturation; 3) defoliation 15 days after the first defoliation; 4) S-ABA200 mg L-1; 5) S-ABA400 mg L-1; 6) S-ABA600 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
6
0
5
Order By: Relevance
“…Specifically, these effects manifest through the influence of the microclimate within bunches [49], phenolic compounds [50,51], and the flavonol profile [52]. Due to the direct effect of bunch exposure to radiation in the aroma profiles obtained in wines, researchers have investigated the effect of defoliation as a management strategy to increase berry quality and aroma traits, which depends on the cultivar, timing of defoliation, and climatic region [53][54][55][56][57][58][59][60]. These researches demonstrate the importance of fruit exposure to solar radiation and microclimate conditions that are favorable to the development of berry quality traits.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, these effects manifest through the influence of the microclimate within bunches [49], phenolic compounds [50,51], and the flavonol profile [52]. Due to the direct effect of bunch exposure to radiation in the aroma profiles obtained in wines, researchers have investigated the effect of defoliation as a management strategy to increase berry quality and aroma traits, which depends on the cultivar, timing of defoliation, and climatic region [53][54][55][56][57][58][59][60]. These researches demonstrate the importance of fruit exposure to solar radiation and microclimate conditions that are favorable to the development of berry quality traits.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum total concentration of polyphenols was associated with 600 mg/L in 'Isabel' grapes. Pessenti et al (2019Pessenti et al ( , 2020 also found an increase in anthocyanin content in 'Primitivo' and 'Malbec' varieties with the use of S-ABA at veraison stage.…”
Section: Introductionmentioning
confidence: 84%
“…Além disso, a relação entre flavonoides e compostos fenólicos sobre a qualidade do vinho é de extrema importância, especialmente em vinhos com potencial de envelhecimento e amadurecimento (Würz, Allebrandt, Filho, Bem, Brighenti, Outemane, et al, 2018). Pessenti et al (2019) verificaram que a aplicação de S-ABA proporcionou desfolha de até 60% na altura dos cachos com dose de 600 mg L -1 , isso contribui para o aumento de antocianinas e polifenóis totais na cv. Malbec.…”
Section: Fonte: Autoresunclassified
“…A expressão das antocianinas depende de fatores internos, como o enântiomero S do ácido abscísico (S-ABA), que induz o fator de transcrição MYB1A, proteína encarregada de regular a transcrição de genes que compõem a rota biossintética das antocianinas das uvas tintas (Jeong et al, 2004;Pastore et al, 2013). Vários trabalhos sugerem que aplicações exógenas de S-ABA antecipam a época de colheita, aumentando as concentrações de antocianinas e proantocianinas nas cascas das uvas, com considerável melhoria em sua coloração, proporcionando maior uniformidade e qualidade (Koyama et al, 2019;Pessenti et al, 2019;Pessenti et al, 2017).…”
Section: Introductionunclassified